The efficacy of Kangaroo-Mother care to the clinical outcomes of LBW and premature infants in the first 28 days: A meta-analysis of randomized clinical trials - Zhu, Zhen; Wang, Xinchen; Chen, Wenzeng; Pei, Shuping; Wang, Qingmin; Guan, Hailian; Zhu, Guang (Frontiers in Pediatrics, 2023)
Objective The objective of this study was to systematically determine the benefits of Kangaroo-Mother Care (KMC) on the clinical outcomes of low birthweight (LBW) and preterm infants. Methods For this study, the following databases were retrieved for articles published until November 2021: PubMed, Web of Science, EBSCO, and the Cochrane library. The primary clinical outcome was mortality between enrollment and 28 days. The secondary clinical outcomes were the mean duration of hospital stay, hypothermia, sepsis, exclusive breastfeeding at the end of the neonatal period, and exclusive breastfeeding at discharge. Results We conducted a meta-analysis, which included 17 RCTs, involving overall 17,668 participants. The results of this meta-analysis showed that KMC could reduce the primary clinical outcome of mortality between enrollment and 28 days (RR: 0.80, 95% Cl: 0.71–0.91, p < 0.01). For the secondary clinical outcomes, KMC had a varying degree of benefits on the mean duration of hospital stay (SMD: −0.96, 95% Cl: −1.02–0.90, p < 0.001), hypothermia (RR: 0.45, 95% Cl: 0.27–0.75, p < 0.01), and sepsis (RR: 0.79, 95% Cl: 0.70–0.89, p < 0.001). The exclusive breastfeeding at the end of the neonatal period and exclusive breastfeeding at discharge of KMC had benefits, which was not statistically different though (OR: 2.16, 95% Cl: 0.55–8.41, p = 0.27; OR: 1.16, 95% Cl: 0.82–1.64, p = 0.39, respectively). Conclusions KMC was decreased mortality in LBW and premature infants between enrollment and 28 days. In addition, KMC also had a favorable effectiveness on the secondary clinical outcomes, such as mean duration of hospital stay, hypothermia, sepsis. Moreover, KMC also had a slight effectiveness on exclusive breastfeeding at the end of the neonatal period and exclusive breastfeeding at discharge.